2018
DOI: 10.3390/ijms19061627
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for Signaling in Biodiagnosis and Treatment of Infectious Diseases

Abstract: Advances in nanoparticle-based systems constitute a promising research area with important implications for the treatment of bacterial infections, especially against multidrug resistant strains and bacterial biofilms. Nanosystems may be useful for the diagnosis and treatment of viral and fungal infections. Commercial diagnostic tests based on nanosystems are currently available. Different methodologies based on nanoparticles (NPs) have been developed to detect specific agents or to distinguish between Gram-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 208 publications
(281 reference statements)
0
22
0
Order By: Relevance
“…Metallic nanoparticles have found diversified applications in the area of electronics, food, and, most profoundly, several biomedical-related fields, especially for their antimicrobial potential and also for their use as a diagnostic tool (Klebowski et al, 2018;Kumar et al, 2018;Azharuddin et al, 2019;Moutsiopoulou et al, 2019). The nano-sized metal-based particles have also been considered as promising tools for targeted drug delivery (Patra et al, 2018), imaging (Chen et al, 2018), sensors (Colino et al, 2018), synthetic inhibitors (Ma et al, 2018), etc. Nanomaterials have strikingly unique physicochemical properties (Ahmed et al, 2017), such as large surface area to mass ratio, ultra-small size, and high reactivity, which impart unusual mechanical (Guo et al, 2013), optical (Jackson and Halas, 2001), electrical, and chemical properties to as-formed particles.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic nanoparticles have found diversified applications in the area of electronics, food, and, most profoundly, several biomedical-related fields, especially for their antimicrobial potential and also for their use as a diagnostic tool (Klebowski et al, 2018;Kumar et al, 2018;Azharuddin et al, 2019;Moutsiopoulou et al, 2019). The nano-sized metal-based particles have also been considered as promising tools for targeted drug delivery (Patra et al, 2018), imaging (Chen et al, 2018), sensors (Colino et al, 2018), synthetic inhibitors (Ma et al, 2018), etc. Nanomaterials have strikingly unique physicochemical properties (Ahmed et al, 2017), such as large surface area to mass ratio, ultra-small size, and high reactivity, which impart unusual mechanical (Guo et al, 2013), optical (Jackson and Halas, 2001), electrical, and chemical properties to as-formed particles.…”
Section: Introductionmentioning
confidence: 99%
“…One could argue that the last decade has witnessed a rise in nanomedicine, with many kinds of NPs being investigated and applied into the clinics, but the nanodrugs that have been approved for their clinical use, or that are actually being investigated in clinical trials are mainly anti-tumoral agents, supplements, imaging contrasts and agents, drug-delivery vehicles, anesthetics (Anselmo and Mitragotri, 2019), and even as biosensors for the detection of infectious diseases (Colino and Millán, 2018), but little to no advances have been made in regards to ANPs into their clinical application, which reflects the importance of this window of opportunity.…”
Section: Translation To the Clinical Setting: Are Nanoparticles Safe mentioning
confidence: 99%
“…These results indicate that silver nanoparticles exhibit anti‐QS properties, and thus can interrupt these signaling pathways within biofilms. In addition, gold nanoparticles, titanium dioxide nanoparticles, and zinc oxide nanoparticles have been reported to have anti‐QS activity. Xu et al showed that CeO 2 nanoparticles decreased biofilm formation through interference of the QS system by generating ROS.…”
Section: Antibiofilm Mechanisms Of Nanoparticles At Different Stages mentioning
confidence: 99%